ASSESSMENT OF OSTEOPOROSIS AND ANAEMIA RISK IN PATIENTS ON ANTICONVULSANT THERAPY - Varghese, Angel P.; Philip, Biji; Krishnakumar, Megha; Kuriakose, Fijomon; Rodrigues, Prudence A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To assess the incidence of osteoporosis and anaemia in patients on anticonvulsant therapy and to educate those under risk. Methods: A prospective observational study was conducted on 50 study participants. The Bone mineral density (BMD), vitamin D, hematological parameters and peripheral smear were noted. Data analyzed using different statistical methods. Patient information brochures for osteoporosis and anaemia were distributed to those on chronic anti-epileptic drug (AED) therapy. Results: The prevalence of osteoporosis was 16% and osteopenia 22%. The BMD of subjects showed an Insignificant reduction in BMD when compared with a standard reference value for south asian population (*P>0.05). The mean BMD in single therapy group was higher compared with multiple therapy groups. BMD of the enzyme-inducing class was less compared with non-enzyme inducing class but was not significant (P>0.05). Duration of therapy was compared with BMD of patients showed a negative correlation. The relationship between duration of therapy and hematological parameters showed a negative correlation (r =-0.128). The mean haematological parameters in single AED therapy were higher when compared with multiple AED therapy. The study demonstrated 40% microcytic hypochromic and 4% macrocytic hypochromic morphology. Conclusion: Chronic therapy with AEDs possesses a significant risk of developing osteoporosis and anaemia. The incidence rate varies according to the type, duration, and mode of therapy. Early detection and management through diet exercise or pharmacotherapy will decrease the incidence of unwanted effects due to AEDs and improve the quality of life. Keywords: Bone mineral density, Antiepileptic drug, Osteoporosis